Crystal Structure and Activity of the Endoribonuclease Domain of the piRNA Pathway Factor Maelstrom. - Matsumoto, N.; Sato, K.; Nishimasu, H.; Namba, Y.; Miyakubi, K.; Dohmae, N.; Ishitani, R.; Siomi, H.; Siomi, M.C.; Nureki, O. (Cell reports, 2015)
PIWI-interacting RNAs (piRNAs) protect the genome from transposons in animal gonads. Maelstrom (Mael) is an evolutionarily conserved protein, composed of a high-mobility group (HMG) domain and a MAEL domain, and is essential for piRNA-mediated transcriptional transposon silencing in various species, such as Drosophila and mice. However, its structure and biochemical function have remained elusive. Here, we report the crystal structure of the MAEL domain from Drosophila melanogaster Mael, at 1.6 Å resolution. The structure reveals that the MAEL domain has an RNase H-like fold but lacks canonical catalytic residues conserved among RNase H-like superfamily nucleases. Our biochemical analyses reveal that the MAEL domain exhibits single-stranded RNA (ssRNA)-specific endonuclease activity. Our cell-based analyses further indicate that ssRNA cleavage activity appears dispensable for piRNA-mediated transcriptional transposon silencing in Drosophila. Our findings provide clues toward understanding the multiple roles of Mael in the piRNA pathway.